Tragedy of the common pool resources and environmental ethics individually liable to global warming - Castilla, Juan Carlos (Acta Bioethica, 2015)
The tragedy of the commons (overexploitation, pollution) is a metaphor well anchored in the literature. The air is a common pool resource and private property does not exist. The global warming of the planet, caused by excess greenhouse gas emissions (CO2, NO2, methane), generated by human activities and consuming society, which are stored in the high atmosphere causing climatic changes, is today a tragedy. We live in a new Era, that of the Antrophocene. Monocentric solutions to this tragedy: top-down —for instance the Kyoto Protocol of 1997— have failed. The article highlights the urgent need to implement polycentric solutions to face the tragedy: bottom-up, individual and collective actions in concurrence with top-down strategies. This needs to be based in the installation of a new environmental responsible ethic, for instance based in the individual responsible Kutz ethic principle. For this is needed to promote, as soon as possible, a postmodern environmental science, with credibility and a true democratization of knowledge. Moreover, there is a need for environmental alphabetization of our society based on hard knowledge about climatic changes and global warming, in all dimensions: negative, positive, new opportunities. The use of massive communication tools may be the key to achieve the goal.